2022
DOI: 10.3390/v14081604
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of the Emerging Genogroup of Infectious Bursal Disease Virus Infection in Broiler Farms in South Korea: A Nationwide Study

Abstract: Infectious bursal disease (IBD), caused by IBD virus (IBDV), threatens the health of the poultry industry. Recently, a subtype of genogroup (G) 2 IBDV named G2d has brought a new threat to the poultry industry. To determine the current status of IBDV prevalence in South Korea, active IBDV surveillance on 167 randomly selected broiler farms in South Korea from August 2020 to July 2021 was conducted. The bursas of Fabricius from five chickens from each farm were independently pooled and screened for IBDV using v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 42 publications
0
16
0
Order By: Relevance
“…G2 has been further geographically divided into the sub-lineages G2a, G2b, G2c, and G2d. Recently, studies have shown that G2d, the dominant genogroup, is highly prevalent in Asian countries, including China, Malaysia, Japan, and South Korea, and is a new threat to poultry farms [ 4 , 5 , 6 ]. Previous studies have shown that this new variant of IBDV could cause more severe pathological lesions than existing variant strains [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…G2 has been further geographically divided into the sub-lineages G2a, G2b, G2c, and G2d. Recently, studies have shown that G2d, the dominant genogroup, is highly prevalent in Asian countries, including China, Malaysia, Japan, and South Korea, and is a new threat to poultry farms [ 4 , 5 , 6 ]. Previous studies have shown that this new variant of IBDV could cause more severe pathological lesions than existing variant strains [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, studies have shown that G2d, the dominant genogroup, is highly prevalent in Asian countries, including China, Malaysia, Japan, and South Korea, and is a new threat to poultry farms [ 4 , 5 , 6 ]. Previous studies have shown that this new variant of IBDV could cause more severe pathological lesions than existing variant strains [ 4 ]. In addition, current vaccines do not provide efficient protection against this novel variant; therefore, an updated antigen-matched vaccine against G2d variant IBDV is urgently needed to protect domestic poultry [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Korea [39], Malaysia [26], India [40], Pakistan [41,42], and Bangladesh [12,20], but it has also been observed in many European [18,43], African [44][45][46][47], and North/South American countries [16,[48][49][50]. These A3B3 genotype viruses were apparently emerged from the early reassortment of the "very virulent" segment A of the European strains around the 1980s and 1990s [51,52] and the "early-Australian" vaccine-originated segment B of the Australian IBDVs around the 1970s [8, 33,53,54].…”
Section: Discussionmentioning
confidence: 99%
“…Since 2017, nVarIBDV has been widely prevalent and has caused critical damage to major poultry breeding regions in China [ 7 , 10 , 52 ] and has also been reported in Japan [ 8 ], Korea [ 9 , 13 ], and Malaysia [ 11 , 12 ]. Atypical IBD caused by nVarIBDV pose a new threat to the poultry industry.…”
Section: The Newly Emerging Nvaribdvmentioning
confidence: 99%
“…In China, IBD was first detected in Beijing and Guangdong in 1979 and rapidly spread to the main poultry areas of this country [ 4 , 5 , 6 ]. In recent years, the sudden prevalence of a novel variant of IBDV (nVarIBDV) in eastern Asia, including China, causing subclinical symptoms in chickens, has brought new threats and challenges to the poultry industry [ 7 , 8 , 9 , 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%